Crystallization Mechanism of Gel-Derived SiO2-TiO2 Amorphous Nanobeads Elucidated by High-Temperature In Situ Experiments - Zandonà, Alessio; Véron, Emmanuel; Helsch, Gundula; Canizarès, Aurélien; Deubener, Joachim; Allix, Mathieu; Genevois, Cécile (Crystal Growth and Design, 2023)
SiO2-TiO2 amorphous nanobeads with a TiO2 content up to 50 mol % were synthesized by sol-gel spray drying. Their crystallization during heat treatments was then characterized by in situ high-temperature techniques including X-ray diffraction, Raman spectroscopy, and particularly high-resolution transmission electron microscopy. Intrinsic nanoscale chemical modulations could be identified already in the as-prepared nanobeads and were shown to play a major role for the nonisochemical precipitation of TiO2 nanocrystals during heating experiments: the size and compositional contrast of such fluctuations progressively evolved and increased until the emergence of long-range ordering. The formation of TiO2 polymorphs occurred according to Ostwald’s rule of stages, with the metastable TiO2(B) phase acting as a precursor to stabilize anatase and rutile. The temporary appearance of TiO2(B) nanocrystals at early annealing stages was interpreted as the first direct experimental observation of subcritical crystalline nuclei.
CRIS-Team Scopus Importer:2023-06-09